Estereotipos sobre el envejecimiento en jóvenes universitarios de la carrera de Psicología Clínica de la Universidad Nacional de Loja, periodo académico 2022 – 2023 - Ludeña Castillo, Doraliza del Cisne (2023)
The objective of this research work is to determine the prevalence of negative stereotypes about aging in a group of university students before and after participating in an intergenerational program. The study was experimental, with a quantitative and cross-sectional approach. The total sample was 24 students, of which 12 formed the experimental group, participating in an intergenerational program, and 12 students in the control group. The evaluation instruments used were the sociodemographic interview and the Questionnaire of Negative Stereotypes towards Old Age (QNSOA). The pre and post-test results reflect a reduction in negative stereotypes against aging in the experimental group that maintained contact with older adults who are part of the intergenerational program, while in the control group, the presence of negative stereotypes did not show any variation. These results show the importance of intergenerational contact in the positive perception of aging. Finally, a promotion proposal focused on the reduction of stereotypes and the promotion of positive attitudes toward aging has been designed